2014
DOI: 10.5897/ajb2013.13561
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and phenotypic characterization of shigatoxigenic Escherichia coli (STEC) and enteropathogenic E. coli (EPEC) from piglets and infants associated with diarrhoea in Mizoram, India

Abstract: Limited information is available on shiga toxin producing Escherichia coli (STEC) in pigs and infants from Aizawl, Mizoram and North Eastern region of India. This cross sectional study was conducted on faecal samples from pigs and infants to detect and characterize of STEC and enteropathogenic E. coli (EPEC). Serogrouping, molecular and phenotypic characterizations were done by standard molecular and cytotoxic assays. Out of 48 E. coli strains isolated from 320 diarrhoeic fecal samples of piglets, 44 belonged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Among all the DEC, EPEC found to be the most common pathotypes for diarrheal infection in Mizoram which is much higher than the previous report [15]. Recent studies from other part of India also found higher occurrence of EPEC compared to EIEC among diarrheal samples [8, 16, 22].…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…Among all the DEC, EPEC found to be the most common pathotypes for diarrheal infection in Mizoram which is much higher than the previous report [15]. Recent studies from other part of India also found higher occurrence of EPEC compared to EIEC among diarrheal samples [8, 16, 22].…”
Section: Discussionmentioning
confidence: 78%
“…Thus, the exact burden of E. coli diarrhea among the hospitalized children across India especially Northeast India is still unclear. In the present study, the samples were collected from Mizoram, located in the North Eastern part of India adjoining to Myanmar and Bangladesh where limited study has been conducted on the prevalence of diarrhea associated with DEC [15, 21]. This is the first report on an in-depth study on the prevalence of EPEC and EIEC associated with diarrhea in children less than 5 years of age in North-eastern Indian population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations